Community Assistance in Promotion Strategy and Tourism Services of Puncak Pato - Fuja Novitra; Selma Riyasni; Dea Stivani Suherman; Festiyed Festiyed; Yenni Darvina (Fakultas MIPA Universitas Negeri Padang, 2026)
Puncak Pato possesses rich natural and cultural potential, yet its tourism promotion and service quality remain limited. This community engagement program aimed to strengthen local capacity in developing promotion strategies and improving tourism services. The activities involved socialization, training, focus group discussions, and field mentoring. Post-test results showed a significant improvement, with an average of 87.5% correct responses, particularly in cultural understanding, hospitality ethics, and basic photography and videography skills (90–100%). The program also produced an output in the form of promotional videos of Nagari Batu Bulek, collaboratively created and shared on social media as digital promotion media. These achievements demonstrate the community’s enhanced digital literacy, creativity, and confidence in managing local tourism independently. Overall, the program contributed to strengthening Puncak Pato’s branding and competitiveness while promoting sustainable community-based tourism development.